P1715CORRELATION OF DONATED KIDNEY MASS AND GRAFT FUNCTION IN RECIPIENTS OF LIVING DONOR KIDNEY TRANSPLANTATION. (6th June 2020) - Silva, Filipa; Pestana, Nicole; Ribeiro, Catarina Isabel; Carneiro, Diogo; Madanelo, Mariana; Tavares, Joana; Pedroso, Sofia; Almeida, Manuela; Malheiro, Jorge; Dias, Leonídio; Silva Ramos, Miguel; Martins, La Salete; et al.
Abstract: Background and Aims: Kidney volume has been proven to be a surrogate marker of nephron mass and renal function in living donors. Although many studies correlate the kidney mass with renal donors' function after donation, few studies have compared the donated kidney mass with estimated glomerular filtration rate (eGFR) in the kidneýs recipients. The purpose of this study is to examine the relationship between donor kidney volume and post-transplantation graft function by using computerized tomography to obtain renal volumes. Method: Clinical data off all donor and recipient pairs undergoing live donor kidney transplantation (KT) at our institution between January 2008 and December 2017 (n=195) were reviewed. The volume of the kidney selected for transplant was determined using volume calculating software and correlate to transplant recipient eGFR. Results: All metrics of donor kidney volume (DKV): DKV alone, ADK adjusted for weight, body mass index (BMI) or body surface area (BSA), correlated significantly with eGFR (all with p<0, 001) at 1 year after KT, with DKV/BSA having the highest correlation (r=0, 431). Hence, recipients were divided into terciles according their DKV/BSA (cm 3 /m 2 ): tercile 1 (DKV/BSA between 49, 7-77, 5, n=64), tercile 2 (78-95, 2, n=63) and tercile 3 (95, 4-176, n=63). eGFR differences between groups at each time point were all significant (P<0.05), except for the comparison between T1 and T2 at month 6 (figure 1) Significant risk factors for eGFR<60 ml/min at 1-year were: acute rejection (AR) at 1-year (OR=4.116, P=0.018); calculated PRA>0% (OR=2.075, P=0.039); higher donor age (OR per unit=1.033, P=0.047); and peritoneal dialysis modality (in comparison with preemptive KT: OR=3.232, P=0.013). Higher (T3) DKV/BSA tercile (in comparison with T1: OR=0.306, P=0.004) was protective of this outcome. Patients that experienced AR at 1-year had significantly lower DKV/BSA, particularly those with acute cellular rejection (ACR). The median follow-up was 4, 8 years (IQR: 3.2-7.5). The censored graft survival by DKV/BSA terciles at 10 years were 59, 3% for group 1, 91.3% for group 2 and 91.1% for group 3 (figure 3). Conclusion: Our study demonstrates that transplantation of donor-recipient pairs with lower DKV/BSA ratio were associated with significantly worse graft function and higher incidence of AR. This data suggests that a larger mass of nephrons remaining adjusted to recipient's weight seems to predict a better long-term eGFR. This method can be useful in order to identify patients at risk for a low eGFR after KT and, in cases of multiple potential donors, optimize donor selection.